HUBUNGAN ANTARA FAKTOR DETERMINAN UTAUT DENGAN MINAT DOKTER GIGI TERHADAP PENGGUNAAN TELEDENTISTRY: STUDI PILOT - Isni Puji Lestari; Risqa Rina Darwita; Febriana Setiawati (Cakradonya Dental Journal, 2023)
The development of Information and Communication Technology (ICT) in the health sector is growing with the existence of teledentistry. This revolution in fact has triggered problems in terms of acceptance of ICT adoption which is still low for both patients, health practitioners and health care providers. Approaches based on behavioral theories are widely used to assess ICT acceptance. The purpose of this article is to explain the concepts and determinants of Unified Theory of Acceptance and Use of Technology (UTAUT) model that can predict the behavioral intention in using teledentistry. This model is the combination of eight theories of technology acceptance behavior that have been widely used in various studies. The UTAUT concept model has four determinants that affect the individual's intention of technology: performance expectancy, effort expectancy, social influence and facilitating conditions. This model also has moderating factors that can affect the relationship between determinants and behavioral intention. This model is proven to provide variation of intention up to 70% when compared to the other theories.